A tradução dos olhos em Clarice Lispector: uma investigação baseada em corpus - Lima, Thereza Cristina de Souza; Camargo, Diva Cardoso de [UNESP] (My University, 2014)
This investigation has as an objective to observe the translation of the word “eyes” and its collocates, in similar and (re)used fragments extracted from two books written by Clarice Lispector, A Descoberta do Mundo, translated by Giovanni Pontiero as Discovering the World and Uma Aprendizagem ou o Livro dos Prazeres, translated by Richard A. Mazzara and Lorri A. Parris as An Apprenticeship or The Book of Delights.Another objective is to identify aspects of normalization found in the respective translations of these fragments. The metodology is situated in the field of Corpus-based Translation Studies, (proposed by Baker, 1993, 1995, 1996, 1999, 2004; studies on normalization by de Scott, 1998); research and project by Camargo 2003a, 2003b, 2004, 2008), and in Corpus Linguistics (studies by Berber Sardinha, 2004); also, it is based on the author’s critical heritage (studies by Gotlib, 1993, 2009; Nunes, B., 1995; Sant‘Anna, 1997; Ruggero 2000; Sá, O., 2000; Franco Júnior, 2000; Ranzolin (1985), Varin, 2002; e Cherem, 2003). The results found in this research enabled to carry out a comparative study among the respective translators concerning tendencies to normalization and show Pontiero’s smaller tendency in relation to the couple of translators Richard A. Mazzara e Lorri A. Parris.

Esta investigação tem como objetivo observar a tradução do vocábulo “olhos” e dos seus colocados, em fragmentos (re)aproveitados e semelhantes extraídos de duas obras de Clarice Lispector A Descoberta do Mundo, traduzida por Giovanni Pontiero como Discovering the World e Uma Aprendizagem ou o Livro dos Prazeres, traduzida por Richard A. Mazzara e Lorri A. Parris como An Apprenticeship or The Book of Delights. Outro objetivo é identificar aspectos de normalização encontrados nas respectivas traduções desses fragmentos. A metodologia situa-se no campo dos Estudos da Tradução baseados em corpus, (proposta de Baker, 1993, 1995, 1996, 1999, 2004; estudos sobre normalização de Scott, 1998); pesquisas e projeto de Camargo 2003a, 2003b, 2004, 2008), e no da Linguística de Corpus (estudos de Berber Sardinha, 2004); também se apoia na fortuna crítica da autora (trabalhos de Gotlib, 1993, 2009; Nunes, B., 1995; Sant‘Anna, 1997; Ruggero 2000; Sá, O., 2000; Franco Júnior, 2000; Ranzolin (1985), Varin, 2002; e Cherem, 2003). Os resultados encontrados nesta pesquisa possibilitaram efetuar um estudo comparativo entre os tradutores em pauta concernente à tendências para normalização e apontam para uma menor tendência por parte de Pontiero em relação à equipe de tradutores formada por Richard A. Mazzara e Lorri A. Parris.
Keywords: Tradução literária; Literatura Brasileira traduzida; Estudos da Tradução Baseados em Corpus; Vocábulos preferenciais; Clarice Liispector